Mechanical characterisation and compressive creep of recycled aggregate limestone calcined clay cement concrete - Mhene, Tafadzwa Mthokozisi (Stellenbosch : Stellenbosch University, 2025)
Mhene, T. 2025. Mechanical Characterisation and Compressive Creep of Recycled Aggregate Limestone Calcined Clay Cement Concrete. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/122d3fad-e2e6-4616-9af2-875469d9de55